The WHO atlas on global resources for persons with intellectual disabilities: a right to health perspective El atlas de recursos para las personas con discapacidad intelectual de la OMS: una visión desde el derecho a la salud - Jocelin Lecomte; Céline Mercier (Instituto Nacional de Salud Pública, 2008)
This paper focuses on the links between the WHO atlas on global resources for persons with intellectual disabilities (Atlas-ID) project and the right to health in international human rights law. The WHO Atlas-ID project initiated by the Department of Mental Health and Substance Abuse of the WHO was designed to collect, compile and disseminate data on intellectual disabilities services and resources throughout the world. The right to health, as linked to all other human rights, brings a set of globally agreed upon norms and standards, and out of these norms arise governmental obligations. Even in countries which have a relatively high standard of living, persons with intellectual disabilities are very often denied the opportunity to enjoy the full range of economic, social and cultural rights. This paper aims at establishing the WHO Atlas-ID and the international human rights instruments as two parts of a holistic approach in regards to State provided services to persons with intellectual disabilities and their families. Este artículo se centra en la relación entre el proyecto Atlas-DI de la OMS y el derecho a la salud en la normativa internacional de derechos humanos. El proyecto Atlas-DI de la OMS, puesto en marcha por el Departamento de Salud Mental y Abuso de Sustancias de la OMS, se diseñó para recolectar, compilar y divulgar datos sobre servicios y recursos para la discapacidad intelectual alrededor del mundo. El derecho a la salud, en su relación con todos los demás derechos humanos, engloba un conjunto de normas y estándares aprobados internacionalmente, y de éstos emanan obligaciones gubernamentales. Incluso en países con estándares relativamente altos de vida, a las personas con discapacidades intelectuales se les niega frecuentemente la oportunidad de disfrutar el espectro total de derechos económicos, sociales y culturales. El objetivo de este artículo es el de establecer el Atlas-DI de la OMS y los instrumentos internacionales en derechos humanos como partes integrantes de un enfoque holístico sobre los servicios provistos por el Estado para las personas con discapacidades intelectuales y sus familias.